Сучасний стан, проблеми та перспективи розвитку споживчої кооперації на місцевому рівні управління (на прикладі Любарської районної спілки споживчих товариств) - Андрощук, Юлія Віталіївна; Androshchuk, Yuliia Vitaliivna (Національний університет "Львівська політехніка", 2023)
Споживча кооперація є важливою складовою економіки України, що робить істотний внесок у розвиток сільських територій, задоволення потреб населення в товарах і послугах, створення робочих місць. Проте в сучасних ринкових умовах споживча кооперація стикається з низкою проблем, що гальмують її розвиток на місцевому рівні. Застарілість матеріально-технічної бази, нестача інвестицій, посилення конкуренції з боку приватного бізнесу вимагають пошуку нових підходів до управління та інноваційного розвитку кооперативних організацій. Тому дослідження шляхів раціоналізації діяльності та розвитку системи споживчої кооперації на прикладі окремих районних спілок є актуальним завданням. Об'єктом дослідження є процес функціонування та розвитку споживчої кооперації на місцевому рівні. Предметом дослідження виступають теоретичні, методичні та прикладні аспекти вдосконалення діяльності Любарської районної спілки споживчих товариств. Метою бакалаврської кваліфікаційної роботи є обґрунтування пропозицій щодо вдосконалення управлінської діяльності та інноваційного розвитку споживчої кооперації на місцевому рівні управління на прикладі Любарської районної спілки споживчих товариств. У першому розділі роботи досліджено теоретичні аспекти функціонування та розвитку споживчої кооперації в Україні, розкрито її роль в економіці та соціальній сфері. Проаналізовано нормативно-правові засади діяльності системи споживчої кооперації. Розглянуто сучасні тенденції та особливості розвитку кооперативного руху. У другому розділі здійснено аналіз діяльності Любарської районної спілки споживчих товариств. Надано загальну характеристику цієї організації, проведено аналіз її виробничо-господарської діяльності та фінансового стану. Ідентифіковано ключові проблеми функціонування та розвитку споживчої кооперації на місцевому рівні на прикладі досліджуваної спілки. Третій розділ виділений обґрунтуванню напрямків вдосконалення діяльності та розвитку споживчої співпраці на місцевому рівні управління. Запропоновано комплекс заходів з підвищення ефективності управління Любарською районною спілкою споживчих товариств, що забезпечує оптимізацію організаційної структури, впровадження стратегічного планування, вдосконалення фінансового менеджменту, управління персоналом, бізнес-процесами. Розроблено інноваційні підходи до розвитку споживчої кооперації в районі, які передбачають модернізацію матеріально-технічної бази, диверсифікацію діяльності, впровадження нових форматів торгівлі та послуг, розвиток кооперативного виробництва, освоєння нових ринкових ніш. Реалізація запропонованих рекомендацій дозволить досягти низки позитивних економічних, соціальних, технологічних та екологічних ефектів, підвищити ефективність та конкурентоспроможність споживчої співпраці на місцевому рівні. Результати дослідження можуть бути використані як у Любарській районній спілці, так і адаптовані для інших організацій системи споживчої кооперації України.

Consumer cooperation is an important component of Ukraine's economy, making a significant contribution to the development of rural areas, meeting the needs of the population for goods and services, and creating jobs. However, in today's market conditions, consumer cooperatives face a number of problems that hinder their development at the local level. The outdated material and technical base, lack of investment, and increased competition from private business require the search for new approaches to the management and innovative development of cooperative organizations. Therefore, the study of ways to rationalize the activities and development of the consumer cooperative system on the example of individual district unions is an urgent task. The object of research is the process of functioning and development of consumer cooperation at the local level. The subject of the study is the theoretical, methodological and applied aspects of improving the activities of the Lubar District Union of Consumer Societies. The purpose of the bachelor's thesis is to substantiate proposals for improving the management activities and innovative development of consumer cooperation at the local level of government on the example of the Lubar District Union of Consumer Societies. In the first section of the work, the theoretical aspects of the functioning and development of consumer cooperation in Ukraine are investigated, its role in the economy and social sphere is revealed. The author analyzes the regulatory and legal framework of the consumer cooperative system. Modern trends and features of the cooperative movement are considered. The second section analyzes the activities of the Lubar District Union of Consumer Societies. A general description of this organization is provided, an analysis of its production and economic activities and financial condition is carried out. The key problems of the functioning and development of consumer cooperation at the local level are identified on the example of the studied union. The third section is devoted to substantiating the directions for improving the activities and development of consumer cooperation at the local level of government. The author proposes a set of measures to improve the efficiency of management of the Lubar District Union of Consumer Societies, which ensures optimization of the organizational structure, implementation of strategic planning, improvement of financial management, personnel management, and business processes. Innovative approaches to the development of consumer cooperation in the district have been developed, which include modernization of the material and technical base, diversification of activities, introduction of new formats of trade and services, development of cooperative production, and development of new market niches. Implementation of the proposed recommendations will allow to achieve a number of positive economic, social, technological and environmental effects, increase the efficiency and competitiveness of consumer cooperation at the local level. The results of the study can be used both in the Lubar District Union and adapted for other organizations of the consumer cooperation system of Ukraine.
The current state, problems and prospects for the development of consumer cooperation at the local level of administration (on the example of the Lubar District Union of Consumer Societies)
Keywords: 6.281.00.00; споживча кооперація; інноваційний розвиток; місцеве управління; ефективність; конкурентоспроможність; матеріально-технічна база; диверсифікація діяльності; кооперативне виробництво; consumer cooperation; innovative development; local governance; efficiency; competitiveness; material and technical base; diversification of activities; cooperative production. List of used literature sources 1. Apopiy V. V. Consumer cooperation of Ukraine: features of development and modern vision / V. V. Apopiy // Black Sea Economic Studies. - 2018. - Issue 35(1). - С. 20-24. - Access mode: http://nbuv.gov.ua/UJRN/bses_2018_35(1)__6. 2. Volkova N.I.; Kryvenko L.V. Features of management of social development of consumer cooperation in Ukraine. Business Inform. 2020. № 1. С. 90-95. 3. Hryniuk N.A. European trends in the development of consumer cooperation: lessons for Ukraine / N.A. Hryniuk // Young scientist. 2018. - № 4 (56). - С. 776-779. 4. Methodological principles of ensuring the competitiveness of consumer cooperation enterprises. Bulletin of KNTEU. 2021. № 4. С. 78-91. 5. Orel Y. Prospects for the post-war economic recovery of Ukraine: the realities of today. 6. Innovative development of consumer cooperation in Ukraine. Economy and state. 2020. № 2. С. 56-60